The effect of accelerated aging on the interface of jute textile reinforced concrete. (November 2016) - Fidelis, Maria Ernestina Alves; Toledo Filho, Romildo Dias; Silva, Flávio de Andrade; Mechtcherine, Viktor; Butler, Marko; Hempel, Simone
Abstract: In this work the degradation mechanisms of concrete reinforced with natural jute textile are discussed. Double-sided pullout tests were performed on specimens reinforced with polymer-coated and uncoated jute fabrics. To obtain a composite with an enhanced durability performance a matrix with partial replacement of the Portland cement by metakaolin was used. Before testing, the specimens were subjected to accelerated aging conditions. After a curing period of 28 days in water the samples were exposed to a temperature of 40 °C and a relative humidity of 99% over 28, 56, 90, 180 and 365 days. Microstructural analyses were performed to evaluate the degradation of the jute yarn and the fiber-matrix interphase using an environmental scanning electron microscope. Thermogravimetric analysis was carried out in order to evaluate the calcium hydroxide content. The pullout results showed that coated fabrics formed a stronger bond than did the uncoated. For ordinary Portland cement matrix the maximum fiber pullout force decreased up to 85% after six months of accelerated aging. In the MK matrix the degradation process was retarded substantially. Polymer coatings improved the bond between fiber and matrix and reduced fiber degradation.